The 2017 Inspire Challenge: Innovation Strategies for Digital Agriculture - CGIAR Platform for Big Data in Agriculture (2018)
This study of the Inspire Challenge in light of innovation strategy looked in part at countries and geographic areas targeted by digital innovators, with an eye toward identifying features of enabling environments for these data-driven solutions to take root.